Features of the development and clinical course of pneumothorax in patients with a new coronavirus infection - K. V. Medvedev; K. E. Borta; M. A. Protchenkov; E. I. Valyukh (Журнал инфектологии)
New coronavirus infection (COVID-19) is a modern global problem that requires the rapid development of diagnostic and treatment methods, as well as the study of pathological effects on body tissues. Due to severe damage to the respiratory organs, special attention is paid to the study of pneumothorax as a manifestation of gas syndrome, one of the complications of COVID-19.The purpose of the study was to assess the incidence of pneumothorax as a complication of COVID-19, the features of the development of the pathological process, and to determine the criteria for treatment tactics.Materials and methods. In total, for the period from April 2020 to May 2022 at the Clinical Infectious Diseases Hospital named after. S.P. Botkin treated 31532 patients with a confirmed diagnosis of COVID-19. As part of this study, the case histories of 316 patients with clinical manifestations of gas syndrome were retrospectively analyzed. All patients were diagnosed with COVID-19, the diagnostic criterion of which was a positive result of the PCR test – the detection of RNA in a swab taken from the nasopharynx and oropharynx.Results. Analysis of case histories showed that severe COVID-19 occurs in all age groups. Collapse of half of the lung was observed in most cases (59 patients). The main treatment method for pneumothorax was Bulau drainage. At the same time, in 47 patients (32%) this method required active aspiration. In 37 patients (26%), drainage was corrected and the pleural cavity was re-drained. In 37 patients, the result of hospitalization was a fatal outcome, the main causes of which were severe pneumonia and/or severe immunodeficiency, 75 patients (52%) were discharged from the hospital in a stable condition.Conclusions. The occurrence of pneumothorax in patients with COVID-19 is characterized by late onset, protracted course, the formation of purulent complications and a high incidence of fatal outcomes, which do not always correlate with the severity of pneumonia.